Launching the SnifferV and Sniffer4D multigas detectors into the active crater of the Poás Volcano in Costa Rica using unmanned aerial systems - Godfrey, Ian (2023)
There are two Sniffer4D V2 devices we have been deploying in the field for scientific research with the Laboratory of Atmospheric Chemistry. We have successfully tested for volcanic emissions at the Turrialba volcano, Irazú volcano, Poás volcano, Arenal volcano and Tenorio volcano in Costa Rica. Sniffer4D - VOCs, O2, SO2, CO, CO2, PM 1, 2.5,10, NO2, O3, NO2 + O3 which was used at the Poás Volcano National Park in Costa Rica during February and April of 2022 was now paired with another device specifically configured for volcanic emissions. The SnifferV (Volcanic) - SO2, CO, CxHy, H2S, CHL, CO2, H2 and HF. These Sniffer devices log longitude and latitude, temperature and humidity and calculate the area tested per each measurement which allowed us to measure the exact fumaroles with precision. There were 3 objectives for our trip to the Poas Volcano National Park 1. The first objective was to attach the SnifferV to the Aki-01 and conduct a flight with this drone system to the degassing fumaroles next to Laguna Caliente inside the active volcano crater of the Poás Volcano National Park. 2. The second objective was to walk with both Sniffer devices to the dormant crater of the Poas Volcano National Park named the Botos Lagoon. 3. The third mission was to hike in between these two craters Laguna Caliente and Botos Lagoon and find an acceptable control station on the eastern rim of the active crater to take gas readings with both Sniffer units.